Research on the Innovation of English Educational Models in Chinese Universities in the Context of Artificial Intelligence - Mengting Yuyi, Ying He (Forest Chemicals Review)
The application of artificial intelligence technology plays an important role in innovating universities’ English educational models. However, given the incomplete understanding of the application mode and concept of artificial intelligence technology by teachers and learners and the imperfect construction of their own artificial intelligence teaching platform, some colleges and universities in China have not fully embraced artificial intelligence educational models. To fully adopt artificial intelligence technology in college English educational innovation, colleges and universities should not only enhance English teachers’ and learners’ understanding and application of artificial intelligence technology, but also should consider adding artificial intelligence factors to the educational evaluation system, and to improve the the development of artificial intelligence platform in English curriculum development.